Abscisic acid induced freezing tolerance in chilling-sensitive suspension cultures and seedlings of rice - Shinkawa, Reiko (BioMed Central, 2013)
BACKGROUND: The role of abscisic acid (ABA) as a possible activator of cold acclimation process was postulated since endogenous levels of ABA increase temporarily or constitutively during cold-hardening. Exogenous application of ABA has been known to induce freezing tolerance at ambient temperatures in in vitro systems derived from cold hardy plants. Yet, some cell cultures acquired much greater freezing tolerance by ABA than by cold whilst maintaining active growth. This raises questions about the relationships among ABA, cold acclimation and growth cessation. To address this question, we attempted to 1) determine whether exogenous ABA can confer freezing tolerance in chilling-sensitive rice suspension cells and seedlings, which obviously lack the mechanisms to acquire freezing tolerance in response to cold; 2) characterize this phenomenon by optimizing the conditions and compare with the case of cold hardy bromegrass cells. RESULTS: Non-embryogenic suspension cells of rice suffered serious chilling injury when exposed to 4°C. When incubated with ABA at the optimal conditions (0.5-1 g cell inoculum, 75 μM ABA, 25-30°C, 7–10 days), they survived slow freezing (2°C/h) to −9.0 ~ −9.3°C (LT(50): 50% killing temperature) while control cells were mostly injured at −3°C (LT(50): -0.5 ~ −1.5°C). Ice-inoculation of the cell suspension at −3°C and survival determination by regrowth confirmed that ABA-treated rice cells survived extracellular freezing at −9°C. ABA-induced freezing tolerance did not require any exposure to cold and was best achieved at 25-30°C where the rice cells maintained high growth even in the presence of ABA. ABA treatment also increased tolerance to heat (43°C) as determined by regrowth. ABA-treated cells tended to have more augmented cytoplasm and/or reduced vacuole sizes compared to control cultures with a concomitant increase in osmolarity and a decrease in water content. ABA-treated (2–7 days) in vitro grown seedlings and their leaves survived slow freezing to −3°C with only marginal injury (LT(50): -4°C) whereas untreated seedlings were killed at −3°C (LT(50): -2°C). CONCLUSIONS: The results indicate that exogenous ABA can induce some levels of freezing tolerance in chilling-sensitive rice cells and seedlings, probably by eliciting mechanisms different from low temperature-induced cold acclimation.